Naringenin, a Food Bioactive Compound, Reduces Oncostatin M Through Blockade of PI3K/Akt/NF-κB Signal Pathway in Neutrophil-like Differentiated HL-60 Cells - Na-Ra Han; Hi-Joon Park; Seong-Gyu Ko; Phil-Dong Moon (Foods)
Oncostatin M (OSM) plays a crucial role in diverse inflammatory reactions. Although the food bioactive compound naringenin (NAR) exerts various useful effects, including antitussive, anti-inflammatory, hepatoprotective, renoprotective, antiarthritic, antitumor, antioxidant, neuroprotective, antidepressant, antinociceptive, antiatherosclerotic, and antidiabetic effects, the modulatory mechanism of NAR on OSM expression in neutrophils has not been specifically reported. In the current work, we studied whether NAR modulates OSM release in neutrophil-like differentiated (d)HL-60 cells. To assess the modulatory effect of NAR, enzyme-linked immunosorbent assay (ELISA), quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting, and immunofluorescence assay were employed. While exposure to granulocyte-macrophage colony-stimulating factor (GM-CSF) induced elevated OSM release and mRNA expression, the elevated OSM release and mRNA expression were diminished by the addition of NAR in dHL-60 cells. While the phosphorylation of phosphatidylinositol 3-kinase, protein kinase B (Akt), and nuclear factor (NF)-κB was upregulated by exposure to GM-CSF, the upregulated phosphorylation was inhibited by the addition of NAR in dHL-60 cells. Consequently, the results indicate that the food bioactive compound NAR may have a positive effect on health (in health promotion and improvement) or may play a role in the prevention of inflammatory diseases.